Concepções e percepções sobre promoção de saúde em universitários de um curso de medicina - Maluf, Ângela Regina Leonesi (2010)
From the new concept of health, understood as a result of multiple factors in a dynamic process, the health care of individuals and society are increasingly under the influences of the Health Promotion theme, which has progressively been presented and determinant. In this context, the relationship between health, prevention and health promotion concepts must be precisely understood in order that the health professionals offer an appropriate treatment to health problems of subjects and society. Therefore, it is emphasized the importance of the professional training according to the guidelines and principles of the Promotion of Health. Thus, the aim of this research was to analyze the conceptions and perceptions about health promotion of last year medical university students at Universidade Federal do Triângulo Mineiro (UFTM). This was a descriptive research with qualitative and quantitative approach, involving sixty undergraduates who answered to a self-administered questionnaire, anonymously, containing questions relating to conceptions and perceptions about health promotion and public health. For the quantitative analysis were used the descriptive statistics and for the qualitative data the thematic content analysis. From the 60 participants of both sexes, aged between twenty three and twenty nine years old, 38% reported having a preference for working in the Medical Clinic area against 5% in primary care area. Regarding to the context of performance, 41.7% reported preferring the contexts of secondary and tertiary care against 3.3% preferring primary care. 70% of students understand the concept of prevention as a way of preventing diseases and the health concept such as the WHO. About the idea of health promotion, 23.4% and 20% reported understanding it as a preventive actions and health education, respectively. About the medical action proposed for the medical health promotion, it was observed that it has been dominated by the community action (40%) and preventive actions (28.3%). Regarding to students' perceptions about the integration level between the theoretical content and practical activities, 21% reported a gap between theory and practice and 15% considered that there is little involvement on the training, followed by 11.7% who reported the scarcity of resources and 10% that graduation has curative approach. So, we concluded that (i) the students have an inadequate and incomplete understanding about the health, prevention and health promotion concepts; (ii) doctors prefer areas of a higher payment, better objectivity and a lower bond with patients; (iii) the level of theory and practice integration in academic activities is unsatisfactory. All this data can be considered a reflection of a medical education model mismatching with the Health Promotion guidelines and distant from the real necessities of subjects and society.